Olanzapine: Association Between a Typical Antipsychotic Drug and Aortic Calcification - Zhang, Chao; Zheng, Dongdong; Feng, Weijing; Zhang, Huanji; Han, Feng; He, Wanbing; Liu, Aiting; Huang, Hui; Chen, Jie (Frontiers in Cardiovascular Medicine, 2021)
Aims: This study concentrates on the relationship between antipsychotic drugs (APDs) and aortic calcification. Methods: All 56 patients with schizophrenia were divided into two groups according to aortic calcification index. APD equivalent dose was calculated via defined daily doses method. Results: In schizophrenia patients with higher aortic calcification index scores, APD equivalent doses were lower. APD equivalent dose was negatively related to aortic calcification index. Although equivalent APD dose in patients without olanzapine treatment was negatively related to aortic calcification index, it seems that equivalent APD dose did not associate with aortic calcification. Conclusion: Aortic calcification is negatively associated with APD dose in schizophrenia patients. Olanzapine seems to be vital to the relationship between aortic calcification and APD treatment.